Floristic diversity of Nossa Senhora das Dores neighborhood in Santa Maria, RS - Schwab, Natalia Teixeira; Girardi, Leonita Beatriz; Neuhaus, Mauricio; Backes, Fernanda Alice Antonello Londero; Bellé, Rogério Antônio; Menegaes, Janine Farias (Ornamental Horticulture, 2014)
Wooded areas in the urban context contribute significantly for improving quality of society’s life. Diagnosing such areas is very important for the development of future afforestation planning of a city. Thus, the objective of this work was to identify, by means of a quali-quantitative inventory, the plant species in Nossa Senhora das Dores neighborhood, in Santa Maria, RS, in the period from February to April, 2010. We found 99 botanical species distributed in 47 families, so the neighborhood can be considered as having great plant diversity. The species Lagerstroemia indica L., Tipuana tipu (Benth.) Kuntze and Syagrus romanzoffiana (Cham.) Glassman showed higher frequency on the public roads of the neighborhood. Many species were inadequate to the afforestation of sidewalks, such as, Ficus benjamina L., Inga marginata Willd., Hovenia dulcis Thunb., Melia azedarach L., among others. Suitability and renewal of some species are recommended to the Nossa Senhora das Dores neighborhood so that the dwellers can better enjoy the urban green.